More than nothing? Auditing business studies - HARNEY, Stefano (Institutional Knowledge at Singapore Management University, 2012)
This paper argues that business school scholarship can be seen as the example par excellence of what we are calling extreme neo-liberalism. By extreme neo-liberalism we mean the coexistence in the same sphere of extreme externalization of costs and extreme regulation of the sources of value. We argue that this condition is most obvious in the research audits conducted in Britain, and spreading globally, audits that record both the extreme externalization in business scholarship of all the sources of the wealth expropriated by business, and at the same time, regulate the very labour that produces this extreme self-regulation. Although this self-regulated labour regards itself as complete, and although it regards its acts of externalization as acts of self-making, we consider the relation between pedagogy and scholarship in order to show how this pervasive form of self-regarding simply does not hold. We conclude by noting that if business scholarship persists in defining itself against all that makes wealth possible, and thus making itself, logically at least, worthless, it also opens the possibility of starting an investigation of wealth, worth and value, from another point of view, one not dependant of completing business, but competing with it.